Combining Straw Mulch with Nitrogen Fertilizer Improves Soil and Plant Physio-Chemical Attributes, Physiology, and Yield of Maize in the Semi-Arid Region of China - Kashif Akhtar; Weiyu Wang; Ivica Djalovic; P. V. Vara Prasad; Guangxin Ren; Noor ul Ain; Muhammad Riaz; Yongzhong Feng; Gaihe Yang; Ronghui Wen (Plants, 2023)
Mulching and nitrogen (N) fertilization are the main drivers for sustainable crop production. The sole use of nitrogen fertilizer threatened both the physiology and production of maize in rain-fed areas. Therefore, we proposed that wheat straw mulching with N fertilization would increase maize yield by improving soil fertility, physiology, and nitrogen use efficiency. A two-year field study evaluated the effects of CK (control), N (nitrogen application at 172 kg ha−1), HS (half wheat straw mulch, 2500 kg ha−1), HS+N (half wheat straw, 2500 kg ha−1 plus 172 kg N ha−1), FS (full wheat straw, 5000 kg ha−1), and FS+N (full wheat straw, 5000 kg ha−1 plus 172 kg N ha−1) on maize growth, physiology, and biochemistry. Compared with the control, the FS+N treatment resulted in the increase of 56% photosynthetic efficiency, 9.6% nitrogen use efficiency, 60% nitrogen uptake, 80% soluble sugar, 59% starches, 48% biomass, and 29% grain yield of maize. In addition, the FS+N regime increased 47%, 42%, and 106% of soil organic carbon and available P and N content in comparison with the control. Maize grain and biomass yields were positively correlated with N uptake, photosynthesis, soil organic carbon, and soil available N and P contents. Conclusively, the use of wheat straw at 5000 kg ha−1, along with 172 kg N ha−1, is a promising option for building a sustainable wheat–maize cropping system to achieve optimal crop yield and improved plant and soil health in a semi-arid region of China.